Biomarkers in the field of obesity and its related comorbidities. (April 2014) - Katsareli, Efthymia A; Dedoussis, George V
Abstract : Introduction: The prevalence of obesity has increased dramatically in the last decades both in children and adults and is now considered a major health problem. It is associated with numerous comorbidities such as hypertension, dyslipidemia, diabetes and subsequent cardiovascular disease (CVD). One of the mechanisms that connect obesity with these comorbidities is the secretion of so-called adipocytokines or adipokines by the adipose tissue itself. Most adipokines with pro-inflammatory properties are overproduced with increasing adiposity, whereas some adipokines with anti-inflammatory or insulin-sensitizing properties, like adiponectin, are decreased. This dysregulation of adipokines production may promote obesity-linked metabolic disorders and CVD. Except adipokines a wide complex network of chemicals balances pro-inflammatory and anti-inflammatory effects. Areas covered: In this review, we summarize the role of various adipokines and other chemicals associated with obesity and its related cardiometabolic comorbidities, with a special focus on recent evidence showing their potential role as biomarkers whose expression are indicative of obesity and its complications. Expert opinion: Biomarkers associated with obesity, type 2 diabetes (T2D) and CVD could prove beneficial for early identification, proper treatment and good life assurance. Unfortunately, the complexity of biological pathways interactions is such that further research is necessary before any of these markers could reach an accurate diagnostic value.